Application of TGT Type Cooperative Model With Kahoot to Improve Cognitive Learning Outcomes of Senior High School Students - Rahmayanti, Dwi; Zulhelmi, Zulhelmi; Putra, Romi (Journal of Indonesian Science Teachers, 2024)
This research aims to determine the increase in student learning gains by implementing the TGT-type cooperative model through Kahoot media on mechanical wave material in class XI SMA N 2 Singingi. The research uses Quasi-Experimental Design type of research with a